The Effectiveness of Claim Queue Services and Participant Reception on the Onsite Queue System - Arfandi Nur; Popong Nurhayati; Linda Karlina Sari (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The study specifically seeks to identify factors influencing participant acceptance, analyze the service load of the manual queuing system, and provide recommendations for effective claim service load management. A mixed-methods approach was used, combining quantitative surveys and qualitative in-depth interviews. Data were analyzed using the Technology Acceptance Model (TAM), Structural Equation Modeling–Partial Least Squares (SEM-PLS), and the Multiple Channel Queuing System framework. Results show that social influence does not significantly affect perceived usefulness, but has a significant effect on perceived ease of use. Furthermore, perceived ease of use significantly influences perceived usefulness and behavioral intention, while perceived usefulness does not significantly affect behavioral intention. Behavioral intention, in turn, has a significant effect on actual system use. While participants generally demonstrate high digital literacy, formal organizational communication channels remain underutilized. Analysis of the manual queuing system also indicates that service waiting times have not met established performance targets. This study provides an integrated analysis combining TAM, SEM-PLS, and Multiple Channel Queuing System modeling to evaluate public service performance. Findings offer strategic recommendations to optimize queue management and enhance service efficiency across branches.